The Drowning Index: Implementation in Drowning, Mechanical Asphyxia, and Acute Myocardial Infarct Cases. Issue 2 (15th February 2014) - Wardak, Khalil S.; Buchsbaum, Robert M.; Walyzada, Frozan
Abstract Drowning is a diagnosis of exclusion based on circumstantial and autopsy correlation. Sugimura proposed a threshold value of 14.1 for the Drowning Index (DI), the ratio of lung and pleural fluid to spleen weight, as a surrogate marker to diagnose drowning. We questioned the use of DI in diagnosing drowning. We compared DI between three groups—drowning, mechanical asphyxia, and myocardial infarct—seen at Broward MEO from 2008 to 2009. Only 9.4% of 53 drownings exceeded the DI threshold of 14.1, while 30% of 10 mechanical asphyxias and 40% of 10 myocardial infarcts had DI >14.1. Sensitivity for the DI test was <10% and specificity 60–70%. Median DI values for all groups were <10. Mann–Whitney U‐test was not statistically significant between groups. The DI is neither sensitive nor specific and lacks any utility in the diagnosis of drowning.